2012
DOI: 10.1186/1465-9921-13-34
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of diagnostic guidelines and putative biomarkers in lymphangioleiomyomatosis

Abstract: BackgroundLymphangioleiomyomatosis is a rare disease occurring almost exclusively in women. Diagnosis often requires surgical biopsy and the clinical course varies between patients with no predictors of progression. We evaluated recent diagnostic guidelines, clinical features and serum biomarkers as diagnostic and prognostic tools.MethodsSerum vascular endothelial growth factor-D (VEGF-D), angiotensin converting enzyme (ACE), matrix metalloproteinases (MMP) -2 and -9, clinical phenotype, thoracic and abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 30 publications
5
43
0
1
Order By: Relevance
“…Since MMPs are secreted as inactive zymogens, which require proteolytic cleavage for activation, we measured pro-and activated MMP-9 in serum and urine using gelatin zymography as previously described [12,22].…”
Section: Mmp and Vascular Endothelial Growth Factor D Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since MMPs are secreted as inactive zymogens, which require proteolytic cleavage for activation, we measured pro-and activated MMP-9 in serum and urine using gelatin zymography as previously described [12,22].…”
Section: Mmp and Vascular Endothelial Growth Factor D Measurementsmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs), can degrade extracellular matrix, and can affect cell growth, invasion, angiogenesis and inflammation [10]. MMP-2 and -9 are overexpressed in the serum of females with LAM [11,12] and MMP-1, -2, -9 and -14 are strongly expressed in the lungs of patients, particularly adjacent to cysts where disrupted collagen and elastic fibres are observed [13,14]. Therefore, inhibition of MMP activity could reduce lung destruction in LAM.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs), which can degrade extracellular matrix, are produced by LAM cells and have been implicated in the formation of lung cysts in LAM, especially MMP-1, MMP-2, MMP-9 and MMP-14, which are elevated in the serum and/or expressed in lung tissue adjacent to cysts [32][33][34][35]. Furthermore, MMPs are known to affect cell growth, invasion, inflammation and angiogenesis [36].…”
mentioning
confidence: 99%
“…These findings are concordant with those of previous studies that found no association between VEGF-D levels and lung function impairment. ( 38 - 40 ) …”
Section: Discussionmentioning
confidence: 99%